Pulmonary valve replacement: a new paradigm with tissue engineering - Carlos Rúben Lima de Almeida Pinto (2022)
Background: Prevalence of congenital heart diseases worldwide is around 9 per 1000 newborns, 20% of which affect the pulmonary valve or right ventricular outflow tract. As survival after surgical repair of these defects has improved over time, there is the need to address the long-term issues of older children and young adults with "repaired" congenital heart diseases. This review aims to review the performance of traditional pulmonary valves and understand how tissue engineering-based valves can improve the management of these patients. Methods: Research was performed on PubMed/MEDLINE, ScienceDirect, Scopus and ResearchGate databases to identify the most recent articles to review the different type of valves used for pulmonary valve replacement nowadays, and also in ClinicalTrials.gov to evaluate the latest outcomes of tissue engineered pulmonary valves in clinical trials. Results: The most used valves are the mechanical and bioprosthetic valves. Despite improving patients' quality of life, these effects are suboptimal due to their limitations, such as durability, inability to grow or adapt to hemodynamic changes. Among all tissue engineered heart valves analyzed, decellularized homografts are already used in clinical practice and are associated to better outcomes. However, based on the data obtained, we believe that the most promising tissue engineered pulmonary valve is based upon in situ pulmonary valve with a bioresorbable scaffold. Conclusions: Tissue engineered pulmonary valves still have a long away to be considered "standard of care". Although, apparently, they potentially have the ability to overcome limitations that traditional valves currently demonstrate in clinical practice.